Pendampingan Penulisan Berita melalui Website sebagai Sosialisasi Pemilu di Komisi Pemilihan Umum Kabupaten Kediri - Ellyda Retpitasari; M. Ilham Aditya Pratama; Imas Condro Kinasih; Siti Amanah; Zafirah Quroatun ‘Uyun; Afif Muthoharoh (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Becomes a media platform used by government agencies in the delivery of information. Ahead of the election, the KPU of Kediri Regency intensively socialized the election to increase community election participation. The purpose of this research is to provide assistance to participants in the process of producing news published through the website platform. The method used in this assistance is the Participatory Action Research method. Through the PAR method, this program focuses on honing the potential of students in writing news through a website platform. The results of this mentoring activity are that participants are able to understand website news, provide motivation to participants in writing website news, and are able to write website news for the KPU of Kediri Regency within the time frame of August to October 2023 with a total of 24 website news.